1980
DOI: 10.1021/jm00186a021
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive 5,6-diarylpyridazin-3-ones

Abstract: The synthesis of a series of 5,6-diarylpyridazinones is described. Some members of this series display an antihypertensive effect in both the spontaneously hypertensive rat (SHR) model and the deoxycorticosteroid (DOCA) model of hypertension. The most potent compounds in the series have halogen substituents on the 5,6-diphenyl rings, a beta-substituted alkyl group at the 2 position of the ring, and acetyl or cyano substituent at the 4 position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In addition, various compounds incorporating a 3(2H)-pyridazinone ring have been synthesized and their pharmacological activities have been reported [10][11][12] . Recently it was reported that a considerable number of 3(2H)-pyridazinone derivatives have analgesic activity [6,[13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various compounds incorporating a 3(2H)-pyridazinone ring have been synthesized and their pharmacological activities have been reported [10][11][12] . Recently it was reported that a considerable number of 3(2H)-pyridazinone derivatives have analgesic activity [6,[13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…These pyridazinones are important intermediates in the synthesis of biologically active pyridazines such as the βblocker Prizidilol [4,42,44]. But, also in the class of the pyridazinones themselves a lot of biologically active compounds can be found: 6-aryl-3(2H)-pyridazinones such as the cardiotonic agent Zardaverine [44], analgesic 4,6diaryl-3(2H)-pyridazinones [52], and antihypertensive 5,6diaryl-3(2H)-pyridazinones [53]. To the best of our knowledge in the literature only a few examples of 5-substituted 4-aryl-, 4-substituted 5-aryl-or 4,5-diaryl-3(2H)-pyridazinones can be found [5,[54][55][56][57].…”
Section: Mechanism Of the Suzuki Stille And Buchwald-hartwigmentioning
confidence: 99%
“…The original DPP compounds were synthesized as antihypertensives [14,15], and some of them had herbicidal activity [16]. In a toxicological study, mitotic figures were found in renal tissue [17,18].…”
Section: Introductionmentioning
confidence: 99%